PENGARUH KARAKTERSITIK GURU TERHADAP MOTIVASI DAN POLA BELAJAR SISWA - Helsa Fitra P; Ahmad Swandi; Sri Rahmadhanningsih; Ulfah Syam; Rampeng Rampeng; Restu Januarty (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
Motivation is a series of attitudes and values that influence individuals to achieve specific things according to individual goals that can be obtained from within oneself, the people around them, and the environment. The purpose of this research is to identify how the influence of the characteristics possessed by a teacher on the motivation and learning patterns of vocational students in remote areas. The type of research used was a mix-method, with a sample of 29 vocational students in one of the districts of West Halmahera. Data analysis is quantitative data from observation, questionnaires, and in-depth interviews. Based on the results of the study, various information was obtained, namely, the characteristics possessed by the teacher incredibly had an influence on student motivation and learning patterns. The standard or example of learning is the teacher